(untitled) (TAJ: Journal of Teachers Association, 2023)
Introduction: Non-alcoholic fatty liver disease (NAFLD) is a chronic liver condition that affects up to one-third of adults in developed nations. NAFLD refers to a group of non-alcoholic diseases that are histologically and clinically distinct. Fatty liver (NAFL, steatosis hepatitis) and steatohepatitis can lead to cirrhosis and rare cases of hepatocellular carcinoma. Materials and Methods: This was a cross-sectional descriptive study conducted in the medicine department, Rajshahi medical college, Rajshahi, among ninety-one T2DM patients. The study population included outdoor patients as well as hospitalized consecutive 91 patients (50 Urban and 41 Rural) in the medicine department with type 2 DM diagnosed according to the American Diabetes Association (ADA) 2011 criteria. NAFLD was detected and graded using abdominal ultrasonography and blood pressure, BMI, waist circumference, HbA1c, lipid profile, and liver function tests. All data were analyzed by SPSS 16, and p-value <0.05 was assumed as statistically significant in this study. Results: A total of 91 patients were enrolled during the study. NAFLD prevalence was higher in urban patients (54.54%) than in rural patients (45.45%). Males were affected more than female patients in both groups. Patients in the urban population had higher weight, waist circumference, hip circumference, and BMI and were diagnosed with NAFLD at a younger age than those in the rural group. Metabolic syndrome was shown to be prevalent in both groups. Conclusion: The prevalence of NAFLD was shown to be greater in the urban population compared to the rural population, with male patients being more impacted than female patients. Although the risk factors for NAFLD were similar in both the study groups, better anthropometric parameters (lower weight), waist circumference, hip circumference, and BMI had a role in reduced prevalence of NAFLD in rural as compared to urban population patients. TAJ 2022; 35: No-2: 151-158